PENERAPAN APLIKASI SISTEM KOMPARASI METODE K-NEAREST NEIGHBOR DAN NEURAL NETWORK DALAM MENENTUKAN KEPUASAN PELAYANAN WALI MURID PADA SEKOLAH DASAR - PUJI ASTUTI; SURANTO SAPUTRA (LPPM, 2017)
This study aims to create a school service system to guardians, with comparative research or comparative study that is by comparing the KNN and Neural Network will be known whether the school service to the student guardian satisfactory or not.This research activity, conducted by collecting library materials related to the taking of the title. Furthermore, researchers also directly visited the place of research to conduct surveys and do data retrieval that will be used in further research.With this research, the school will be able to make quicker decisions to provide services to guardians. This study used Comparative Method K-Nearest Neighbor And Neural Network. The process of data retrieval for this research is taken through administrative services, learning process and learning outcomes. Thus the data of this school service will be very helpful in decision making by the school.